The role of ion pairs and ion activity in classification of ground waters for irrigation in Erbil plain - Esmail, Akram O.; Salih, Hemn O. (Sulaimani Journal for Pure and Applied Sciences, 2014)
This study was conducted to investigate the effect of ion pairs and ion activity on classification of ground waters. The investigation was included chemical analyses of water of (38) wells, according to Richards (US) classification (1954) the water of (18) wells having C2S1 class, water of (16) wells having C3S1 class and the water of (4) wells were not suitable for irrigation since they have C4S1 class. Correcting ion pairs and ionic activity caused the change of water class of well number (38) from C4S1 to C4S2 class. On the other hand, correcting ion pairs and ion activity caused the change of water classes of wells number (24, 25 and 27) from moderate class to good class and has changed water of well number 30 from bad to moderate class, the similar effect of ion pairs and ion activity noticed in some other classifications.
Keywords: Water classification; ion pairs; ion activity; Ground water